Synthesis of α-ketoamides via gold(I) carbene intermediates - Wu, Zuozuo; Adak, Tapas; Dietl, Martin C.; Wang, Tao; Hu, Chao; Shi, Hongwei; Krämer, Petra; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organic letters, 2022)
α-Ketoamides have been found to be an important functional group in a broad spectrum of inhibitors such as the Corona virus and other viruses. Here we report an unprecedented gold-catalyzed 2-fold reaction of a bromoalkyne with anthranils. Hydrolysis of the initial product then directly leads to α-ketoamides. Water addition to the intermediate α-iminoimidoyl halides delivered α-ketoamides from a broad range of bromoalkynes.